Cartera vencida del servicio de agua potable del GAD del cantón Ventanas del año 2022. - Rain Gil, Aranzha Millaray (2023)
In this case study, the issue of overdue accounts in the EP-Municipal Water and Sewerage Company of Ventanas Canton was addressed. The problem revolved around the high rate of delinquency among users of this service, resulting in outdated records due to deficiencies in debt collection management and the lack of precise references. The justification lay in the need to improve debt recovery efficiency because the overdue accounts affected the financial sustainability of the institution and had an impact on the quality of basic services provided. The general objective was to analyze the overdue accounts of the company in the year 2022, evaluating both accounts receivable and debt collection management. To achieve this, a mixed methodology was employed, including inductive and deductive methods, as well as research techniques such as interviews and surveys. The results revealed a marked difference between accounts receivable from previous years and those of the year 2022, with a significant increase in overdue accounts in the latter period, accounting for 75.86% of the total accounts receivable for water services. It was also identified that debt collection management had deficiencies, including the absence of an efficient system and issues with notifying users of pending amounts. The importance of training the personnel responsible for debt recovery was emphasized, and key processes such as notifications and legal actions were identified as strategies for addressing overdue accounts.